The Influence of Solvency, Profitability and Company Size on Audit Delay in Property and Real Estate Companies on the IDX 2018-2021 - Thomas Nadeak; H. Nugraha; Imas Purnamasari (Westscience Press, 2024)
The capital market is a mechanism or place where various financial instruments are traded. These instruments include stocks, bonds, mutual funds and derivatives. The main objective of the capital market is to facilitate the flow of funds from parties who have surplus funds (investors) to parties who need funds (companies or government) for operational or investment activities. Understanding the Capital Market, here tells how the Primary Market and Secondary Market issue securities for the first time. The function of the Market is as a source of funding, investment, setting share prices, reselling securities. Talking about variables that discuss audit delay, namely the period of time between the closing date of the company's fiscal year and the date of completion of the audit report by an independent auditor. Audit delay is a major concern because it has an impact on the timeliness of presenting financial reports to stakeholders. This research aims to analyze the influence of Sovability, Profitability and Company Size on Audit Delay in Property and Real Estate Companies on the IDX 2018-2021. The data used in this research is secondary data taken from real estate and Property financial reports. This research is research Quantitative with the sampling technique used is purposive sampling. It is hoped that the results of this research will provide a clear picture of the influence of Solvency, Profitability and Size Companies regarding Audit Delay. And the results of this study become a reference for investors in making more measured decisions.